Geography versus income: The heterogeneous effects of carbon taxation - Charles Labrousse; Yann Perdereau (European Central Bank (ECB), 2025)
The distributive effects of carbon taxation are critical for its political acceptability and depend on both income and geographic factors. Using French administrative data, household surveys, and matched employer-employee records, we document that rural households spend 2.8 times more on fossil fuels than urban households and are employed in firms that emit 2.7 times more greenhouse gases. We incorporate these insights into a spatial heterogeneous-agent model with endogenous migration and wealth accumulation, linking spatial and macroeconomic approaches. After an increase in carbon taxes, we quantify that rural households face 20% higher welfare losses than urban households. In an optimal revenue-recycling exercise, we compare transfers targeting income and geography, and show that neglecting for geography reduces welfare gains by 7%. We conclude that carbon policies should account for spatial differences to improve political feasibility.
Keywords: C61; E62; H23; Q43; Q58; R13; 330; Carbon tax; inequalities; revenue recycling; spatial and macroeconomic models; migration